Ultralow-resistance high-efficiency air filter screen material and preparation method thereof
By setting a low melting point EVA and curing agent's bonding layer on the second mesh layer of the air filter material, the air filter materials in the existing technology are stiffly low and the wind resistance when the hot melting glue bonding under high air volume conditions. The problem of elevated has achieved high -efficiency and low -resistance air filter materials.
Patent Information
- Application Number
- CN202411268153.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing air filter materials have low stiffness under high air volume conditions, resulting in deformation, and the air resistance is increased when using hot melt adhesive to bond the mesh layer and the filter layer.
A bonding layer made of low -melting point EVA and curing agent, the curing agent consists of a crystalline EVA and a curing agent layer. The curing agent layer is a solid curing agent made of sulfenol and epoxy compounds. Time makes the adhesive fully infiltrate the filter layer, improve the composite strength and reduce the wind resistance.
The high composite intensity and low wind resistance of the air filter material are realized, and the wind resistance is reduced to 0.5 to 0.7Pa.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter materials, and in particular to an ultra-low resistance high efficiency air filter material and a preparation method thereof. Background Art
[0002] Air filter material is a filter material used to filter aerosols and dust particles in the air. It is mainly used in household air-conditioning systems, HVAC systems and mobile transportation air-conditioning systems. The air filter materials in the current prior art mainly use electrostatic cotton and electret melt-blown non-woven fabrics as filter layers, among which electrostatic cotton has the characteristics of small wind resistance, low noise and large dust holding capacity.
[0003] Although electrostatic cotton has excellent performance as a filter material, in actual use, due to the large air volume of the air system, a single electrostatic cotton has low stiffness and is easy to deform under large air volume and cannot be used. Therefore, people in this field have optimized the stiffness of electrostatic cotton. The prior art discloses compounding an electrostatic skeleton material on the surface of electrostatic cotton to improve the stiffness of electrostatic cotton. However, in actual application, it is found that the wind resistance of the electrostatic cotton with the composite electrostatic skeleton material will significantly increase to more than 3 Pa, and the cost will be significantly increased. Therefore, in order to solve the above problems, Publication No. CN115230268A proposes compounding an electrostatic skeleton material on both sides of the electrostatic cotton. A method for preparing a mesh cloth, in which the first mesh layer and the filter layer are compounded by a needle-punching process, and the second mesh layer and the filter layer are compounded by a hot-melt adhesive. The prepared air-conditioning filter mesh cloth has low wind resistance and high stiffness, and the wind resistance can reach 1.0-1.9 Pa; in addition, personnel in this field have found that the amount of hot-melt adhesive used in the preparation of the above-mentioned filter material has a greater influence on the wind resistance of the filter material, and the less the amount of hot-melt adhesive used, the greater the wind resistance. In addition, the curing time of the hot-melt adhesive is extremely short, usually only 8-10 seconds. Therefore, in order to ensure the bonding strength, the amount of hot-melt adhesive must be ensured and cannot be too small. Therefore, the hot-melt adhesive will have a greater influence on the wind resistance of the filter layer. Summary of the invention
[0004] In order to overcome the problem in the prior art that using hot melt adhesive to bond the mesh layer and the filter layer will lead to increased wind resistance of the filter material, the present invention provides an ultra-low resistance and high-efficiency air filter material, wherein a bonding layer made of low-melting-point EVA and a curing agent is arranged on the surface of the second mesh layer of the material, the curing agent is composed of crystalline EVA and a curing agent layer on its surface, and the curing agent layer is a solid curing agent made of thiol and epoxy compound. The curing time of the second mesh layer of the material can be extended to 5 to 10 minutes when compounded with the filter layer, and the adhesive can fully infiltrate the surface of the filter layer during compounding, thereby ensuring the composite strength of the mesh cloth and the filter layer and significantly reducing the influence of the adhesive on the filter material, and the wind resistance of the filter material can be reduced to 0.5 to 0.7 Pa.
[0005] The specific technical scheme of the present invention is: An ultra-low resistance and high-efficiency air filter material comprises a filter layer, a first mesh layer bonded to the filter layer, and a second mesh layer bonded to the filter layer, wherein the surface of the second mesh layer is provided with an adhesive, wherein the adhesive comprises 30 to 45 parts of low-melting-point EVA, 5 to 8 parts of high-crystalline EVA, and 10 to 20 parts of a curing agent, and the curing agent is provided on the surface of the crystalline EVA.
[0006] The present invention provides an ultra-low resistance and high-efficiency air filter material, which is composed of a filter layer and a first mesh layer and a second mesh layer respectively compounded on both sides of a filter layer. The wind resistance of the air filter material can be reduced to 0.5-0.7 Pa, and the material has high stiffness, light weight and low wind resistance. The present invention finds that when hot melt adhesive is used to compound the second mesh layer and the filter layer, there is a problem that the curing time is very short and the amount of adhesive is high, resulting in an increase in the wind resistance of the composite material. The curing time of traditional polyolefin hot melt adhesive is usually only 8-10s. Therefore, a certain amount of hot melt adhesive is required when it is used so that the hot melt adhesive can fully infiltrate and bond with the surface of the filter layer. Therefore, the amount of hot melt adhesive is usually controlled at 0.3-0.5g / m 2 , this part of the hot melt adhesive will cause the wind resistance of the filter material to increase.
[0007] The present invention provides an adhesive for the above-mentioned problem, and arranges the adhesive on the surface of the second grid layer in the form of a solid film. The method can significantly reduce the amount of the adhesive, solve the problem that the adhesive has a great influence on the wind resistance of the filter material, and reduce the wind resistance of the filter material to 0.5-0.7 Pa; in addition, the present invention also optimizes the curing time of the adhesive, prolongs the curing time of the adhesive to 5-10 minutes, so that the adhesive has enough time to fully infiltrate the surface of the filter layer during compounding, and ensures the peel strength after curing. The adhesive of the present invention uses low-melting-point EVA as the basic raw material of the adhesive. The low-melting-point adhesive has good fluidity and can better infiltrate the filter layer after melting to ensure the composite strength. In addition, the present invention adds a curing agent and High crystallinity EVA, the curing agent adopts a solid curing agent made of thiol and epoxy resin. The curing agent is a solid curing agent. The low melting point EVA has a lower melting point, and the high crystallinity EVA has a higher melting point. Therefore, the low melting point EVA can be melted first at a lower temperature by heating, and then the high melting point EVA can be melted at a higher temperature. Therefore, the heating rate can be set between the melting points of the low melting point EVA and the high crystallinity EVA to control the melting time of the adhesive, and then the solid curing agent is wrapped by the high crystallinity EVA, and then the high crystallinity EVA is heated to release the wrapped curing agent after melting, and mixed with the low melting point EVA and the melted high crystallinity EVA at the melting temperature of the solid curing agent, and the adhesive is quickly cured.
[0008] Preferably, the raw materials of the curing agent are pentaerythritol tetrakis-3-mercaptopropionate and an epoxy compound in a mass ratio of 0.32 to 2.68:1, and the epoxy equivalent of the epoxy compound is 1500 to 7000.
[0009] Preferably, the adhesive further comprises 10 to 20 parts by mass of a tackifying resin and 10 to 15 parts by mass of a viscosity modifier.
[0010] Preferably, the tackifying resin is one or more of rosin, terpene resin, petroleum resin, thermoplastic phenolic resin and low molecular weight polystyrene.
[0011] Preferably, the viscosity modifier is one or more of cycloalkyl mineral oil, hydrogenated polybutadiene, paraffin, microcrystalline wax, Fischer-Tropsch wax, polyethylene wax, oxidized polyethylene wax and polypropylene wax.
[0012] Preferably, the feature is that the first mesh layer contains polypropylene fibers with a mass ratio greater than 85%, and the second mesh layer contains polypropylene fibers with a mass ratio greater than 85%.
[0013] Preferably, the surface density of the first mesh layer is 25-50 warp threads / 10cm, and the weft threads are 25-50 threads / 10cm; the surface density of the second mesh layer is 20-30 warp threads / 10cm, and the weft threads are 20-30 threads / 10cm; the filter layer is an electrostatic cotton made of polypropylene fiber and polyacrylonitrile fiber in a mass ratio of 65-85:15-40, the fiber diameter of the polypropylene fiber is 1-2dtex, and the fiber diameter of the polyacrylonitrile fiber is 2-4dtex.
[0014] A method for preparing the above-mentioned ultra-low resistance high efficiency air filter material comprises the following steps: The filter layer is made of polypropylene fiber and polyacrylonitrile, and the second mesh layer is connected to the filter layer by a needle punching process; the thiol is heated to 120-200°C, and then an epoxy compound is added to react to form a solid curing agent, the curing agent is crushed to 10-50 μm, and high-crystalline EVA is heated to melt, and the crushed curing agent powder is added to the high-crystalline EVA and mixed evenly to form a curing agent composite, and then the curing agent composite is crushed to 50-100 μm and mixed with molten low-melting-point EVA and coated on the surface of the first mesh layer to solidify into a film; the first mesh layer and the filter layer surface are hot-pressed and quickly cooled to form an ultra-low resistance and high-efficiency air filter material.
[0015] Preferably, the conditions for the hot pressing bonding include: temperature of 120-180° C. and time of 5-10 min.
[0016] Preferably, the conditions of the needling process include: a vehicle speed of 5 to 15 m / min, 1 to 2 needling lines, and a needling direction from the filter layer toward the second mesh layer.
[0017] Compared with the prior art, this application has the following technical effects: The invention provides an ultra-low resistance and high-efficiency air filter material. The surface of the second mesh layer of the material is provided with an adhesive layer made of low-melting-point EVA and a curing agent. The curing agent is composed of a solid curing agent and high-crystallization EVA wrapped on the surface of the solid curing agent. The curing agent layer is a solid curing agent made of thiol and epoxy compound. The curing time of the second mesh layer of the material can be controlled within 5 to 10 minutes when compounded with a filter layer, so as to ensure that the adhesive fully infiltrates the filter layer and ensure the composite strength, so that the prepared air filter material has high composite strength and low wind resistance, and the wind resistance of the air filter material can be reduced to 0.5 to 0.7 Pa. The adhesive is loaded on the second mesh layer to form a film, has good uniformity and uses a small amount of adhesive, and the adhesive will not have a significant effect on the wind resistance of the filter layer. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with the embodiments.
[0019] Embodiment 1: An ultra-low resistance high-efficiency air filter material, comprising a filter layer, a first mesh layer bonded to the filter layer, and a second mesh layer bonded to the filter layer; the first mesh layer has a warp diameter of 0.2 mm, a weft diameter of 0.2 mm, and a gram weight of 10 g / m 2 , surface density warp / weft 24 / 10cm, the warp and width direction of the first mesh layer are 45 degrees; the warp diameter of the second mesh layer is 0.4mm, the weft diameter is 0.4mm, and the gram weight is 90g / m 2 , the surface density of warp / weft is 30 pieces / 10cm, the warp and width directions of the second mesh layer are 90 degrees; the filter layer is an electrostatic cotton made of polypropylene fiber and polyacrylonitrile fiber in a mass ratio of 65:35, the fiber diameter of the polypropylene fiber is 1.5dtex, and the fiber diameter of the polyacrylonitrile fiber is 2.5dtex. The surface of the second mesh layer is provided with an adhesive, and the adhesive includes, by mass, 30 parts of low-melting point EVA, 5 parts of crystalline EVA (melting point 140°C), 10 parts of tackifying resin (CrayValley Company, Wingtack 98), 10 parts of curing agent and 10 parts of viscosity regulator (Honeywell Company, AC 1660).
[0020] A method for preparing the above-mentioned ultra-low resistance high efficiency air filter material comprises the following steps: Step 1: Put polypropylene fiber and polyacrylonitrile into a cotton mixing box and mix them thoroughly, then enter the carding and web laying process to form a filter layer; Step 2: Use a needle punching process to compound the first mesh layer and the filter layer at a speed of 10m / min to form a first mesh layer / filter layer composite, and the needle punching direction is from the filter layer to the second mesh layer; Step 3: After heating 16.2g of pentaerythritol tetra-3-mercaptopropionate to 180°C, 100g of epoxy resin (epoxy equivalent 1500-2000, Kain Chemical YD017) was added to react to prepare a solid curing agent, the curing agent was crushed into 10-50μm, high-crystalline EVA was heated to melt, the crushed curing agent powder was added to the high-crystalline EVA and mixed evenly to prepare a curing agent composite, and then the curing agent composite was crushed into 50-100μm and added to the molten low-melting point EVA (melting point is 120°C) with the curing agent, tackifying resin and viscosity modifier, dispersed and mixed evenly, and then coated on the surface of the first grid layer, cooled and dried to prepare a second grid layer with a surface composite adhesive; Step 4: Press the surface composite adhesive in step 3 onto the uncompounded side of the first mesh layer / filter layer composite in step 2, raise the temperature from 120°C to 160°C within 5 minutes, and then quickly cool and solidify to form an ultra-low resistance high-efficiency air filter material.
[0021] Embodiment 2: An ultra-low resistance high-efficiency air filter material, comprising a filter layer, a first mesh layer bonded to the filter layer, and a second mesh layer bonded to the filter layer; the first mesh layer has a warp diameter of 0.2 mm, a weft diameter of 0.2 mm, and a gram weight of 15 g / m 2 , surface density warp / weft 20 / 10cm, the warp and width direction of the first mesh layer are 45 degrees; the warp diameter of the second mesh layer is 0.3mm, the weft diameter is 0.3mm, and the gram weight is 125g / m 2 , the surface density of warp / weft is 50 pieces / 10cm, the warp and width directions of the second mesh layer are 90 degrees; the filter layer is an electrostatic cotton made of polypropylene fiber and polyacrylonitrile fiber with a mass ratio of 80:20, the fiber diameter of the polypropylene fiber is 1.0dtex, and the fiber diameter of the polyacrylonitrile fiber is 4.0dtex, and the surface of the second mesh layer is provided with an adhesive, which includes 38 parts of low melting point EVA, 7 parts of high crystalline EVA (melting point 140°C), 15 parts of tackifying resin (CrayValley Company, Wingtack 98), 15 parts of curing agent and 12 parts of viscosity modifier (Honeywell Company, AC 1660) by mass; A method for preparing the above-mentioned ultra-low resistance high efficiency air filter material comprises the following steps: Step 1: Put polypropylene fiber and polyacrylonitrile into a cotton mixing box and mix them thoroughly, then enter the carding and web laying process to form a filter layer; Step 2: Use a needle punching process at a speed of 15m / min to compound the first mesh layer and the filter layer to form a first mesh layer / filter layer composite, and the needle punching direction is from the filter layer to the second mesh layer; Step 3: After heating 16.2g of pentaerythritol tetra-3-mercaptopropionate to 180°C, 100g of epoxy resin (epoxy equivalent 3500-7000, KD-213 produced by Guodu) is added to react to prepare a solid curing agent, the curing agent is crushed into 10-50μm, high-crystalline EVA is heated to melt, the crushed curing agent powder is added to the high-crystalline EVA and mixed evenly to prepare a curing agent composite, and then the curing agent composite is crushed into 50-100μm and added to the molten low-melting point EVA (melting point is 100°C) with the curing agent, tackifying resin and viscosity modifier, dispersed and mixed evenly, and then coated on the surface of the first grid layer, cooled and dried to prepare a second grid layer with a surface composite adhesive; Step 4: Press the surface composite adhesive in step 3 onto the uncompounded side of the first mesh layer / filter layer composite in step 2, raise the temperature from 100°C to 160°C within 5 minutes, and then quickly cool and solidify to form an ultra-low resistance high-efficiency air filter material.
[0022] Embodiment 3: An ultra-low resistance high-efficiency air filter material, comprising a filter layer, a first mesh layer bonded to the filter layer, and a second mesh layer bonded to the filter layer; the first mesh layer has a warp diameter of 0.2 mm, a weft diameter of 0.2 mm, and a gram weight of 30 g / m 2 , surface density warp / weft 17 / 10cm, the warp and width direction of the first mesh layer are 45 degrees; the warp diameter of the second mesh layer is 0.4mm, the weft diameter is 0.4mm, and the gram weight is 90g / m 2 , the surface density of warp / weft is 50 pieces / 10cm, the warp and width directions of the second mesh layer are 90 degrees; the filter layer is an electrostatic cotton made of polypropylene fiber and polyacrylonitrile fiber in a mass ratio of 80:20, the fiber diameter of the polypropylene fiber is 1.0dtex, and the fiber diameter of the polyacrylonitrile fiber is 4.0dtex, and the surface of the second mesh layer is provided with an adhesive, which includes 45 parts of low melting point EVA, 8 parts of high crystalline EVA (melting point 140°C), 20 parts of tackifying resin (CrayValley Company, Wingtack 98), 20 parts of curing agent and 15 parts of viscosity modifier (Honeywell Company, AC 1660) by mass; A method for preparing the above-mentioned ultra-low resistance high efficiency air filter material comprises the following steps: Step 1: Put polypropylene fiber and polyacrylonitrile into a cotton mixing box and mix them thoroughly, then enter the carding and web laying process to form a filter layer; Step 2: Use a needle punching process to compound the first mesh layer and the filter layer at a speed of 8m / min to form a first mesh layer / filter layer composite, and the needle punching direction is from the filter layer to the second mesh layer; Step 3: After heating 16.2g of pentaerythritol tetra-3-mercaptopropionate to 180°C, 100g of epoxy resin (epoxy equivalent 3500-7000, KD-213 produced by Guodu) is added to react to prepare a solid curing agent, the curing agent is crushed into 10-50μm, high-crystalline EVA is heated to melt, the crushed curing agent powder is added to the high-crystalline EVA and mixed evenly to prepare a curing agent composite, and then the curing agent composite is crushed into 50-100μm and added to the molten low-melting point EVA (melting point is 100°C) with the curing agent, tackifying resin and viscosity modifier, dispersed and mixed evenly, and then coated on the surface of the first grid layer, cooled and dried to prepare a second grid layer with a surface composite adhesive; Step 4: Press the surface composite adhesive in step 3 onto the uncompounded side of the first mesh layer / filter layer composite in step 2, raise the temperature from 110°C to 160°C within 5 minutes, and then quickly cool and solidify to form an ultra-low resistance high-efficiency air filter material.
[0023] Embodiment 4: An ultra-low resistance high-efficiency air filter material, comprising a filter layer, a first mesh layer bonded to the filter layer, and a second mesh layer bonded to the filter layer; the first mesh layer has a warp diameter of 0.2 mm, a weft diameter of 0.2 mm, and a gram weight of 10 g / m 2 , surface density warp / weft 24 / 10cm, the warp and width direction of the first mesh layer are 45 degrees; the warp diameter of the second mesh layer is 0.4mm, the weft diameter is 0.4mm, and the gram weight is 90g / m 2 , the surface density of warp / weft is 30 pieces / 10cm, the warp and width directions of the second mesh layer are 90 degrees; the filter layer is an electrostatic cotton made of polypropylene fiber and polyacrylonitrile fiber in a mass ratio of 65:35, the fiber diameter of the polypropylene fiber is 1.5dtex, and the fiber diameter of the polyacrylonitrile fiber is 2.5dtex. The surface of the second mesh layer is provided with an adhesive, which includes 30 parts of low-melting point EVA, 5 parts of high-crystalline EVA (melting point 160°C), 10 parts of tackifying resin (CrayValley Company, Wingtack 98), 10 parts of curing agent and 10 parts of viscosity regulator (Honeywell Company, AC 1660) by mass.
[0024] A method for preparing the above-mentioned ultra-low resistance high efficiency air filter material comprises the following steps: Step 1: Put polypropylene fiber and polyacrylonitrile into a cotton mixing box and mix them thoroughly, then enter the carding and web laying process to form a filter layer; Step 2: Use a needle punching process to compound the first mesh layer and the filter layer at a speed of 10m / min to form a first mesh layer / filter layer composite, and the needle punching direction is from the filter layer to the second mesh layer; Step 3: After heating 268g of sorbitol polythioglycolate to 180°C, add 100g of epoxy resin (epoxy equivalent 1500-2000, Kain Chemical YD017) to react to form a solid curing agent, crush the curing agent to 10-50μm, heat the high-crystalline EVA to melt, add the crushed curing agent powder to the high-crystalline EVA and mix evenly to form a curing agent composite, then crush the curing agent composite to 50-100μm, add it to the molten low-melting point EVA (melting point is 120°C) with the curing agent, tackifying resin and viscosity regulator, disperse and mix evenly, and then apply it on the surface of the first grid layer, cool and dry to form a second grid layer with a surface composite adhesive; Step 4: Press the surface composite adhesive in step 3 onto the uncompounded side of the first mesh layer / filter layer composite in step 2, raise the temperature from 120°C to 180°C within 10 minutes, and then quickly cool and solidify to form an ultra-low resistance high-efficiency air filter material.
[0025] Embodiment 5: An ultra-low resistance high-efficiency air filter material, comprising a filter layer, a first mesh layer bonded to the filter layer, and a second mesh layer bonded to the filter layer; the first mesh layer has a warp diameter of 0.2 mm, a weft diameter of 0.2 mm, and a gram weight of 15 g / m 2 , surface density warp / weft 20 / 10cm, the warp and width direction of the first mesh layer are 45 degrees; the warp diameter of the second mesh layer is 0.3mm, the weft diameter is 0.3mm, and the gram weight is 125g / m 2 , the surface density of warp / weft is 50 pieces / 10cm, the warp and width directions of the second mesh layer are 90 degrees; the filter layer is an electrostatic cotton made of polypropylene fiber and polyacrylonitrile fiber with a mass ratio of 80:20, the fiber diameter of the polypropylene fiber is 1.0dtex, and the fiber diameter of the polyacrylonitrile fiber is 4.0dtex, and the surface of the second mesh layer is provided with an adhesive, which includes 38 parts of low melting point EVA, 7 parts of high crystalline EVA (melting point 160°C), 15 parts of tackifying resin (CrayValley Company, Wingtack 98), 15 parts of curing agent and 12 parts of viscosity modifier (Honeywell Company, AC 1660) by mass; A method for preparing the above-mentioned ultra-low resistance high efficiency air filter material comprises the following steps: Step 1: Put polypropylene fiber and polyacrylonitrile into a cotton mixing box and mix them thoroughly, then enter the carding and web laying process to form a filter layer; Step 2: Use a needle punching process at a speed of 15m / min to compound the first mesh layer and the filter layer to form a first mesh layer / filter layer composite, and the needle punching direction is from the filter layer to the second mesh layer; Step 3: After heating 268g of sorbitol polythioglycolate to 180°C, add 100g of epoxy resin (epoxy equivalent 3500-7000, KD-213 produced by Guodu) to react to form a solid curing agent, crush the curing agent to 10-50μm, heat the high-crystalline EVA to melt, add the crushed curing agent powder to the high-crystalline EVA and mix evenly to form a curing agent composite, and then crush the curing agent composite to 50-100μm, add it to the molten low-melting point EVA (melting point is 100°C) with the curing agent, tackifying resin and viscosity regulator, disperse and mix evenly, and then apply it on the surface of the first grid layer, cool and dry to form a second grid layer with a surface composite adhesive; Step 4: Press the surface composite adhesive in step 3 onto the uncompounded side of the first mesh layer / filter layer composite in step 2, raise the temperature from 100°C to 180°C within 10 minutes, and then quickly cool and solidify to form an ultra-low resistance high-efficiency air filter material.
[0026] Embodiment 6: An ultra-low resistance high-efficiency air filter material, comprising a filter layer, a first mesh layer bonded to the filter layer, and a second mesh layer bonded to the filter layer; the first mesh layer has a warp diameter of 0.2 mm, a weft diameter of 0.2 mm, and a gram weight of 30 g / m 2 , surface density warp / weft 17 / 10cm, the warp and width direction of the first mesh layer are 45 degrees; the warp diameter of the second mesh layer is 0.4mm, the weft diameter is 0.4mm, and the gram weight is 90g / m 2 , the surface density of warp / weft is 50 pieces / 10cm, the warp and width direction of the second mesh layer are 90 degrees; the filter layer is an electrostatic cotton made of polypropylene fiber and polyacrylonitrile fiber with a mass ratio of 80:20, the fiber diameter of the polypropylene fiber is 1.0dtex, and the fiber diameter of the polyacrylonitrile fiber is 4.0dtex. The surface of the second mesh layer is provided with an adhesive, which includes 45 parts of low melting point EVA, 8 parts of high crystalline EVA (Thailand Petrochemical UV1070, melting point 160°C), 20 parts of tackifying resin (Cray Valley Company, Wingtack 98), 20 parts of curing agent and 15 parts of viscosity modifier (Honeywell Company, AC 1660) by mass; A method for preparing the above-mentioned ultra-low resistance high efficiency air filter material comprises the following steps: Step 1: Put polypropylene fiber and polyacrylonitrile into a cotton mixing box and mix them thoroughly, then enter the carding and web laying process to form a filter layer; Step 2: Use a needle punching process to compound the first mesh layer and the filter layer at a speed of 8m / min to form a first mesh layer / filter layer composite, and the needle punching direction is from the filter layer to the second mesh layer; Step 3: After heating 268g of sorbitol polythioglycolate to 180°C, add 100g of epoxy resin (epoxy equivalent 3500-7000, KD-213 produced by Guodu) to react to form a solid curing agent, crush the curing agent to 10-50μm, heat the high-crystalline EVA to melt, add the crushed curing agent powder to the high-crystalline EVA and mix evenly to form a curing agent composite, then crush the curing agent composite to 50-100μm, add it to the molten low-melting point EVA (melting point is 110°C) with the curing agent, tackifying resin and viscosity regulator, disperse and mix evenly, and then apply it on the surface of the first grid layer, cool and dry to form a second grid layer with a surface composite adhesive; Step 4: Press the surface composite adhesive in step 3 onto the uncompounded side of the first mesh layer / filter layer composite in step 2, raise the temperature from 110°C to 180°C within 10 minutes, and then quickly cool and solidify to form an ultra-low resistance high-efficiency air filter material.
[0027] Comparative Example 1: Compared with Example 1, in Comparative Example 1, polyolefin hot melt adhesive is used instead of adhesive to compound the first mesh layer and the filter layer, and other conditions are the same as those in Example 1.
[0028] Comparative Example 2: Compared with Example 1, in Comparative Example 2, no curing agent and high-crystalline EVA are added to the adhesive, and other conditions are the same as those in Example 1.
[0029] Comparative Example 3: Compared with Example 1, in Comparative Example 3, no high-crystalline EVA was added to the adhesive, and the other conditions were the same as those in Example 1.
[0030] Comparative Example 4: Compared with Example 1, in Comparative Example 4, the high-crystalline EVA is not coated on the surface of the curing agent, the curing agent and the high-crystalline EVA are crushed and mixed and then added to the low-melting-point EVA, and the other conditions are the same as those in Example 1.
[0031] Test example The air filter materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were tested, and the test items were: wind resistance, peel strength and filtration efficiency; Wind resistance test method: Cut the air filter material into fixed size, place it under constant temperature and humidity conditions (23℃, humidity 50% RH) for 24 hours for pretreatment, and then place it on a filter area of 100cm2 On the TSI 8130A (the aerosol is sodium chloride), adjust the wind speed to 5.3cm / sec, and test the resistance of the air filter material after the wind speed stabilizes; The peel strength test method refers to GB / T8808-1988 T-type peel strength test method for soft composite plastics. The instrument used for the peel test is XLW (PC) intelligent electronic tensile testing machine. Filtration efficiency test method: Cut the mesh cloth into fixed size, place it under constant temperature and humidity conditions (23°C, humidity 50% RH) for 24 hours for pretreatment, then place it on TSI 8130A (aerosol is sodium chloride) with a filtration area of 100cm2, adjust the wind speed to 5.3cm / sec, and test the efficiency of the air filter material after the wind speed stabilizes; The test results are shown in Table 1; Table 1 Test results Resistance (Pa) Peel strength (N / m) Filtration efficiency (%) Example 1 0.51 6.8 81 Example 2 0.54 6.5 82 Example 3 0.59 6.7 83 Example 4 0.68 6.4 72 Example 5 0.69 6.1 72 Example 6 0.72 6.2 74 Comparative Example 1 1.4 5.8 58 Comparative Example 2 / 3.4 / Comparative Example 3 / 3.2 / As shown in Table 1, the ultra-low resistance and high efficiency air filter materials prepared in Examples 1 to 6 have a wind resistance of 0.5-0.7 Pa, a peel strength of 6.1-6.8 N / m, and a filtration efficiency of 72-81%. The material has high composite strength, low resistance, and high filtration efficiency.
[0032] Comparative Example 1 is an air filter material prepared by compounding with polyolefin hot melt adhesive. The wind resistance of Comparative Example 1 is 1.4 Pa, the peel strength is 5.8 N / m, and the filtration efficiency is 58%. From the results of Comparative Example 1 and Example 1, it can be seen that the air filter material prepared in the present application has significantly improved peel strength and filtration efficiency compared with the air filter compounded with hot melt adhesive, and the wind resistance of the filter material is significantly reduced.
[0033] The adhesive in Comparative Example 2 does not contain high-crystalline EVA and curing agent, and its peel strength is only 3.4 N / m. After analysis, it is found that when high-crystalline EVA and curing agent are not added to the adhesive, the fluidity of the low-melting-point EVA is relatively large, and long-term melting will cause the low-melting-point EVA to flow along the fiber flow of the filter layer, resulting in a significant decrease in the peel strength of the final air filter material.
[0034] In Comparative Example 3, no high-crystalline EVA was added, and its peel strength was only 3.2 N / m. After analysis, it was found that, similar to Comparative Example 2, the high-crystalline EVA would form a high-viscosity melt with the low-melting-point EVA after melting. When the high-crystalline EVA was not melted yet, the melted low-melting-point EVA could quickly wet the fiber. After the high-crystalline EVA was melted, the high-crystalline EVA would quickly mix with the low-melting-point EVA to form a high-viscosity melt, ensuring that the melt would not flow quickly so that the melt could be maintained on the surface of the second mesh layer and the filter layer.
[0035] In Comparative Example 4, the high-crystalline EVA is not used to coat the curing agent. In actual operation, it is found that when the high-crystalline EVA and the curing agent are not compounded, the dispersibility of the curing agent in the low-melting point EVA is poor and it is difficult to mix evenly. After the high-crystalline EVA is wrapped on the curing agent, the high-crystalline EVA and the low-melting point EVA have high compatibility and can be evenly dispersed in the low-melting point EVA.
[0036] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. An ultra-low resistance high efficiency air filter material, characterized in that: The invention comprises a filter layer, a first mesh layer bonded to the filter layer and a second mesh layer bonded to the filter layer, wherein the surface of the second mesh layer is provided with an adhesive, wherein the adhesive comprises 30 to 45 parts of low melting point EVA, 5 to 8 parts of high crystalline EVA and 10 to 20 parts of a curing agent, wherein the curing agent is provided on the surface of the crystalline EVA, and the raw materials of the curing agent are thiol and epoxy compound in a mass ratio of 0.16 to 2.68:
1.
2. The ultra-low resistance high efficiency air filter material according to claim 1 is characterized in that: The thiol is one or both of pentaerythritol tetrakis-3-mercaptopropionate and sorbitol polythioglycolate, and the epoxy equivalent of the epoxy compound is 1500-7000.
3. The ultra-low resistance high efficiency air filter material according to claim 1 is characterized in that: The adhesive further comprises 10 to 20 parts of a tackifying resin and 10 to 15 parts of a viscosity modifier by weight.
4. The ultra-low resistance high efficiency air filter material according to claim 3 is characterized in that: The tackifying resin is one or more of rosin, terpene resin, petroleum resin, thermoplastic phenolic resin and low molecular weight polystyrene.
5. The ultra-low resistance high efficiency air filter material according to claim 3 is characterized in that: The viscosity modifier is one or more of naphthenic mineral oil, hydrogenated polybutadiene, paraffin wax, microcrystalline wax, Fischer-Tropsch wax, polyethylene wax, oxidized polyethylene wax and polypropylene wax.
6. The ultra-low resistance high efficiency air filter material according to claim 1 is characterized in that: The first mesh layer contains polypropylene fibers in an amount greater than 85% by weight, and the second mesh layer contains polypropylene fibers in an amount greater than 85% by weight.
7. The ultra-low resistance high efficiency air filter material according to claim 1 or 6, characterized in that: The surface density of the first mesh layer is 25~50 warp threads / 10cm, and the weft threads are 25~50 threads / 10cm. The surface density of the second mesh layer is 20~30 warp threads / 10cm, and the weft threads are 20~30 threads / 10cm. The filter layer is an electrostatic cotton made of polypropylene fiber and polyacrylonitrile fiber in a mass ratio of 65~85:15~40. The fiber diameter of the polypropylene fiber is 1~2 dtex, and the fiber diameter of the polyacrylonitrile fiber is 2~4 dtex.
8. A method for preparing the ultra-low resistance high efficiency air filter material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The filter layer is made of polypropylene fiber and polyacrylonitrile, and the second mesh layer is connected to the filter layer by a needle punching process; After the thiol is heated to 120-200°C, an epoxy compound is added to react to form a solid curing agent, the curing agent is crushed into 10-50 μm, high-crystalline EVA is heated to melt, the crushed curing agent powder is added to the high-crystalline EVA and mixed evenly to form a curing agent composite, and then the curing agent composite is crushed into 50-100 μm and mixed with molten low-melting-point EVA and coated on the surface of the first mesh layer to solidify into a film; the first mesh layer and the filter layer surface are hot-pressed and quickly cooled to form an ultra-low-resistance and high-efficiency air filter material.
9. The preparation method according to claim 8, characterized in that: The conditions for the hot pressing bonding include: a temperature of 120-180° C. and a time of 5-15 min.
10. The preparation method according to claim 8, characterized in that: The conditions of the needling process include: a vehicle speed of 5-15 m / min, 1-2 needling lines, and a needling direction from the filter layer toward the second mesh layer.
Citation Information
Patent Citations
Purification composite material
CN106362485A
Needled / melt-blown / spunbond composite filter material and preparation method thereof
CN110772889A
Powder coating and preparation method thereof
CN112300667A
Air conditioner filtering gridding cloth as well as preparation method and application thereof
CN115230268A